Lipidomic analyses identify injury‐specific phospholipid changes 3 mo after traumatic brain injury. Issue 12 (10th September 2014) - Abdullah, Laila; Evans, James E.; Ferguson, Scott; Mouzon, Benoit; Montague, Hannah; Reed, Jon; Crynen, Gogce; Emmerich, Tanja; Crocker, Madison; Pelot, Robert; Mullan, Michael; Crawford, Fiona
Abstract : Phospholipid (PL) abnormalities are observed in the cerebrospinal fluid of patients with traumatic brain injury (TBI), suggesting their role in TBI pathology. Therefore, PL levels were examined in a TBI mouse model that received 1.8 mm deep controlled cortical impact injury or craniectomy only (control). The rotarod and Barnes maze acquisition and probe tests were performed within 2 wk after injury, with another probe test performed 3 mo postinjury. Liquid chromatography/mass spectrometry analyses were performed on lipid extracts from several brain regions and plasma from injured and control mice collected at 3 mo postinjury. Compared to controls, injured mice with sensorimotor and learning deficits had decreased levels of cortical and cerebellar phosphatidylcholine (PC) and phosphatidylethanolamine (PE) levels, while hippocampal PC, sphingomyelin and PE levels were elevated. Ether PE levels were lower in the cortices and plasma of injured animals. Polyunsaturated fatty acid‐containing PC and PE species, particularly ratios of docosahexaenoic acid (DHA) to arachidonic acid, were lower in the hippocampi and cortices and plasma of injured mice. Given the importance of DHA in maintaining neuronal function and resolving inflammation and of peroxisomes in synthesis of ether PLs, normalizing these PLs may be a useful strategy for treating the chronic pathology of TBI.—Abdullah, L., Evans, J. E., Ferguson, S., Mouzon, B., Montague, H., Reed, J., Crynen, G., Emmerich, T., Crocker, M., Pelot, R., Mullan, M., Crawford, F., Lipidomic analyses identify injury‐specific phospholipid changes 3 months after traumatic brain injury. FASEB J. 28, 5311–5321 (2014). www.fasebj.org